Commercialization of Citizen Data by Digital Platforms: Between Legality and Exploitation - Noviya, Anis; Sagena, Unggul (PT. Anagata Sembagi Education, 2025)
The commercialization of citizens’ personal data has become a core element of digital platform business models through profiling, targeted advertising, and data analytics. The legality of such practices is commonly justified through user consent as the legal basis for data processing. In practice, however, consent is often formalistic and reflects an imbalance of bargaining power between platforms and users. This condition raises legal questions regarding the boundary between lawful data management and digital exploitation of privacy rights. This study aims to analyze the legality of data commercialization by digital platforms and to examine whether such practices constitute exploitation under personal data protection law. Using a normative juridical method with statutory, conceptual, and limited comparative approaches, this study finds a normative conflict between personal data protection principles and data driven economic practices legitimized by consent. Formal compliance does not necessarily ensure substantive privacy protection. The study concludes that restrictive interpretation of consent and stronger platform accountability are required to prevent the normalization of data exploitation in the digital economy.